Prevalence characteristic of BVDV in some large scale dairy farms in Western China - Zhang, Kang; Zhang, Jingyan; Qiu, Zhengying; Zhang, Kai; Liang, Fenfen; Zhou, Qiaoni; Wang, Lei; Li, Jianxi (Frontiers in Veterinary Science, 2022)
The aim of this study was to analyze the prevalence characteristic of Bovine viral diarrhea virus (BVDV) in some large scale dairy farms in Western China. BVDV was detected in 30 samples of bulk tank milk (BTM) collected from 30 large dairy farms in 7 provinces of western China, 93.33% (28/30) of the farms were infected with BVDV, and S/P ratio was over 0.3 in 28 positive farms. The individual status was further estimated in the dairy farm (No. 10) with the highest positive rate (S/P ratio = 1.37) and the dairy farm (No.17) with the lowest positive rate (S/P ratio = 0.39). 200 cows were respectively selected from calf, young cows and lactating cows in farm No.10 and farm No.17 dairy, and the serum sample of each enrolled cow was collected. The individual positive rate of serum antibody (Ab) was 87.17% (523/600) in farm No.10 and 31.33% (188/600) in farm No.17. The individual positive ratio of serum antibody in calves, young cows and lactating cows were 13.92 % (167/1200), 19.58% (235/1200) and 25.75% (309/1200), respectively. BTM Ab of farm No.10 has an S/P ratio more than 1.0, which indicated there were emergent or persistent infection (PI) cases, and further test showed that PI cases were 0.51% in farm No.10. Pathogens were positive in 42.34% (163/385) of nasal mucus samples collected from cows with respiratory symptom, and BVDV cases were 57 in 163 positive samples. Three strains of NCP BVDV-1, one strain of CP BVDV-1, one strain of NCP BVDV-2 and one strain of CP BVDV-2 were successfully isolated. Phylogenetic analysis revealed that the subtypes of BVDV currently prevalent in western China were BVDV-1a, BVDV-1m, BVDV-1q and BVDV-2. The findings suggested that the BVDV infection is serious in some Large Scale Dairy Farms in Western China.